Managing suicidal behaviour in Muslim with depression: issues and challenges - Mat Zin, Nora; Mohd Noor, Hanisah (Zes Rokman Resources, 2017)
Suicide is prohibited in Islam as per a verse in Al Quran (4:29). However, having a suicidal thought is not uncommon in depressed Muslim, although literatures had shown that the rate of suicide generally low among Muslim. Aims: The aim of this paper is to discuss on the issue and challenges in managing suicidal behaviour in Muslim patient based on two illustrated cases of depressive disorder. Two ladies who were different in age but presented with depressive disorder and suicidal thought. The first case was young lady in twenties and the second case was in the fifties. Both of them had tertiary education, almost similar social status and fairly good understanding of religion. They had depressive symptoms and the suicidal thought that was so intent until sometimes they couldn’t handle it. Although the suicidal was part of the depressive symptoms, however it has increased the guilt and sinful thought in them that needs to be tackle cautiously. Treating them with biopsychosocial and spiritual approach eventually help them to recover. The challenges identified such as the issue of suicidality and religion, family engagement, therapist skill and societal stigma will be discussed. Conclusion: Integration of knowledge and understanding of Islamic principle in managing suicidality in depressed Muslim patient are essential to provide a holistic care to the patient. Keywords: suicidal, depression, Islamic principle